2017
DOI: 10.1016/j.yhbeh.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone administration does not affect men's rejections of low ultimatum game offers or aggressive mood

Abstract: Correlative evidence suggests that testosterone promotes dominance and aggression. However, causal evidence is scarce and offers mixed results. To investigate this relationship, we administered testosterone for 48h to 41 healthy young adult men in a within-subjects, double-blind placebo-controlled balanced crossover design. Subjects played the role of responders in an ultimatum game, where rejecting a low offer is costly, but serves to destroy the proposer's profit. Such action can hence be interpreted as non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…The prediction that high testosterone would promote the rejection of unfair offers, based on the findings of earlier studies 11, 15 , was not confirmed. However, our results are in line with those of other studies that reported no effect of testosterone on rejection in the UG 16, 17, 19 . We found a strong main effect of testosterone on offer level, which is consistent with Eisenegger et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The prediction that high testosterone would promote the rejection of unfair offers, based on the findings of earlier studies 11, 15 , was not confirmed. However, our results are in line with those of other studies that reported no effect of testosterone on rejection in the UG 16, 17, 19 . We found a strong main effect of testosterone on offer level, which is consistent with Eisenegger et al .…”
Section: Discussionsupporting
confidence: 93%
“…This finding was replicated by Mehta and Beer 15 both in men and women, but other studies have reported no statistically significant effect of exogenous testosterone on the rejection of inequitable offers 1619 .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Two correlational studies have reported that men and women with relatively high baseline concentrations of testosterone are more likely to reject unfair offers [38,39]. In contrast, pharmacological challenge research in both men and women have not found these effects of testosterone on rejection behavior in the ultimatum game [40,41,42,22]. In a recent study [43], researchers investigated the effect of exogenous testosterone on men's punishment and reward behavior following unfair and fair offers in the ultimatum game.…”
Section: Testosterone and The Ultimatum Gamementioning
confidence: 99%